PERGESERAN TAPAK LAPAN PADA MASYARAKAT MELAYU PALEMBANG ZURIYAT KAPITAN BELA MINAL MUSLIMIN - Duski Ibrahim; Maya Panorama; Nur Fitriyana; Abdul Karim Nasution; Raden Muhammad Fauwaz Diradja (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2021)
The study of the Tread Lapan shift in the Malay community of Palembang zuriyat of the ninth Kapitan Bela minal Muslimim has never been studied. In the history of the global economic development of the Malay community, it is known that this community has played an important role in the economic field. They have succeeded in processing natural resources so that they become superior products needed by local and foreign traders. The community's global economy is supported by eight traditional livelihoods known as tapak lapan. The focus of this research is the shift in the Tapak Lapan of the Malay community to the ninth zuriyat of Kapitan Bela which seems to be the zuriyat of the Ming Dynasty. This type of research is field research with a qualitative descriptive approach. Primary data source for the ninth zuriyat of Kapitan Bela in Palembang. Secondary data is sourced from relevant articles, journals, and books. Data collection techniques through observation, interviews, and documentation. Data analysis techniques are data reduction, data presentation and conclusions. This study resulted in the following findings: (1) Referring to the genealogy and ecofac evidence of the village of Saudagar Koching 3 Ulu Palembang, the Malay community of the ninth zuriyat of Kapitan Bela seems to have come from the Ming Dynasty. (2) Although there are still zuriyat who are engaged in trading, there has been a shift in the eight sites, such as some who work as teachers, lecturers, health workers and work in companies. This shift is due to the desire to live, the desire to get a job and the desire to gain social status. This desire is supported by internal and external factors. Internal factors come from religious teachings and Malay philosophy. External factors are the development of science and technology, education and other family success motivations.